2020
DOI: 10.1177/0194599820927328
|View full text |Cite
|
Sign up to set email alerts
|

Medical Intervention Alone vs Surgical Drainage for Treatment of Peritonsillar Abscess: A Systematic Review and Meta‐analysis

Abstract: Objective Peritonsillar abscesses (PTAs) are common emergency consultations for otolaryngologists. Medical management alone may offer satisfactory treatment without the risk associated with surgical drainage. Therefore, we performed a systematic review of medical treatment alone compared to surgical drainage for the treatment of PTA. Data Sources MEDLINE, EMBASE, Cochrane CENTRAL, and ClinicalTrials.gov. Review Methods Studies comparing the outcomes of medically treated to surgically treated patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(131 reference statements)
1
15
0
Order By: Relevance
“…In a recent meta-analysis of observational studies, there was similarly no difference in treatment failure rates between those treated with surgery or medical management alone. 3 This was again confirmed in a recent large retrospective cohort study. 15 Despite evidence to suggest the utility of medical management alone, we found relatively little uptake of this practice as first-line management in the currently presented study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In a recent meta-analysis of observational studies, there was similarly no difference in treatment failure rates between those treated with surgery or medical management alone. 3 This was again confirmed in a recent large retrospective cohort study. 15 Despite evidence to suggest the utility of medical management alone, we found relatively little uptake of this practice as first-line management in the currently presented study.…”
Section: Discussionsupporting
confidence: 58%
“…Recent evidence indicates that medical treatment alone may result in less pain and faster return to normal oral intake and daily living without an increase in treatment failure or PTA-associated sequelae. 2 , 3 …”
mentioning
confidence: 99%
“…https://doi.org/10.1017/S0022215121001213 of peritonsillar abscess. 19 Similarly, conservative medical management is reported as an effective treatment for co-existent peritonsillar abscess and Covid-19. 20 Given the relative contraindication of corticosteroids in those at higher risk of Covid-19, we recorded more cases of suspected quinsy in group 2 that were managed with antibiotics alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, although we did not perform further subgroup analysis of confirmed cases of quinsy, recent evidence indicates no significant difference in outcomes between medical management and surgical drainage of peritonsillar abscess. 19 Similarly, conservative medical management is reported as an effective treatment for co-existent peritonsillar abscess and Covid-19. 20 Given the relative contraindication of corticosteroids in those at higher risk of Covid-19, we recorded more cases of suspected quinsy in group 2 that were managed with antibiotics alone.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported no difference in failure rate between therapies, but trismus was significantly more prevalent in the ST group. Most recently, in April 2020, Forner et al 6 performed a systematic review and meta-analysis of 33 000 patients from 10 retrospective and 2 randomized, prospective studies further corroborated these findings, reporting no statistically significant difference in the odds of treatment failure for patients treated medically (5.7%) versus surgically (5.5%). Forner et al identified a "major limitation in the current literature" that patients treated medically may be diluted by patients with peritonsillar cellulitis or less severe abscess, as definitive abscess formation may be difficult to confirm based on history and physical examination alone.…”
Section: Introductionmentioning
confidence: 93%